Chapter 4 The Kinesin-3 Family Long-Distance Transporters - Siddiqui, Nida (Taylor & Francis, 2020)
The Kinesin-3s are a family of cargo transporters. They typically display highly processive plus-end-directed motion, either as dimers or in teams, formed via interaction with cargo